Water scarcity: A fact or Fiction for a coastal village of Bangladesh - Mustari, Sohela; Karim, A.H.M Zehadul (MCSER Publishing, Rome-Italy, 2016)
This paper sets out an examination of natural disaster amongst coastal villagers in a developing country, and presents the nature of social vulnerability in collecting drinking and fresh water in their everyday life. Global climate change and geographical location of coastal Bangladesh effects on societal people by creating constraints in having fresh water. To know the nature and sufferings in collecting and getting fresh water, this research used 30 in-depth interviews from the villagers and the intellectuals. Three more Focus Group Discussions were triangulated to increase the reliability of the collected data.